Defining inter-communality between documents, tradition and collective memory: Jewish and non-Jewish capital and labor in early twentieth century Rhodes. Issue 2 (3rd April 2017) - Guidi, Andreas
Abstract: This article deals with the relations between Jews and Non-Jews, especially Greeks, in late and post-Ottoman Rhodes. In the first part, I show that an understanding of the dimension of cosmopolitan Ottoman port cities is necessary for inquiring into the societal dynamics of the post-imperial local context. Secondly, I describe the obstacles for a pluralistic and inter-confessional historiography based on the current trends pursued by Greek and Jewish authors. The economic aspect of the coexistence between Greeks and Jews being a recurrent, yet very generalized and superficial motive in those works, I inquire into relations of individuals in the capital and labour market of Rhodes. In this empirical section, I draw from archival sources to show that inter-communality was far from being an exceptional, a-normal occurrence in different professions, from moneylending to prostitution. Instead, it represented a persistent factor of cooperation, interdependence and occasional conflict. By downplaying any rigid narrative of confessional segregation and coherence, I argue that 'groupist' reading of the history of Rhodes in the twentieth century should be challenged by further efforts towards a polyphonic and inclusive narrative more focused on the social actors.